2007
DOI: 10.1002/14651858.cd005456.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic use of ergot alkaloids in the third stage of labour

Abstract: Background Previous research has shown that the prophylactic use of uterotonic agents in the third stage of labour reduces postpartum blood loss and moderate to severe postpartum haemorrhage (PPH). PPH is defined as a blood loss of 500 mL or more within 24 hours after birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…However, ergometrine and methylergometrine are unstable in heat with an unpredictable bioavailability, which precludes oral use (de Groot 1996). They are vasoconstrictive and increase the risk of hypertension postpartum (Liabsuetrakul 2007). Other side-effects with ergot alkaloids are pain after birth, nausea and vomiting (Liabsuetrakul 2007).…”
Section: Ergometrinementioning
confidence: 99%
See 1 more Smart Citation
“…However, ergometrine and methylergometrine are unstable in heat with an unpredictable bioavailability, which precludes oral use (de Groot 1996). They are vasoconstrictive and increase the risk of hypertension postpartum (Liabsuetrakul 2007). Other side-effects with ergot alkaloids are pain after birth, nausea and vomiting (Liabsuetrakul 2007).…”
Section: Ergometrinementioning
confidence: 99%
“…They are vasoconstrictive and increase the risk of hypertension postpartum (Liabsuetrakul 2007). Other side-effects with ergot alkaloids are pain after birth, nausea and vomiting (Liabsuetrakul 2007).…”
Section: Ergometrinementioning
confidence: 99%
“…Prendiville et al in their Cochrane Systematic review, due to be updated, found that active management halves the risk of postpartum haemorrhage compared with expectant management [4]. Much of this reduction is due to the prophylactic uterotonic drug: [6,7] oxytocin is the drug of choice, as it has comparable impact on blood loss with fewer adverse effects than ergot alkoids [6]. The impact of other components, such as when is best to give the uterotonic [8], when to clamp the cord [9] and whether to use controlled cord traction [10], is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed that plant extracts rich in alkaloids (Liabsuetrakul et al, 2007), glycosides, tannins, flavonoids (Lakshmi et al, 2014), saponins (Dande and Patil, 2012) and steroids have abortifacient potential (Kumar et al, 2012). The abortifacient activity of MEACmay be because of these phytoconstituents acting alone or in combination.…”
Section: Discussionmentioning
confidence: 99%